Inhibition of Notch Signaling Induces Neural Differentiation in Ewing Sarcoma - Baliko, Frank (American Society for Investigative Pathology, 2007)
Cells from Ewing sarcoma exhibit cellular features and express markers, suggesting that the tumor is of neuroectodermal origin. Because Notch signaling regulates the differentiation of neuroectodermal cells during development, we examined the role of Notch signaling in Ewing sarcomas. We found that Ewing sarcomas express Notch receptors, ligands, and the Notch target gene HES1. To determine the functional implications of Notch signaling, we expressed tetracycline-regulated constitutively active, dominant-negative (DN), or wild-type Notch-1 receptors in two Ewing sarcoma cell lines, or we treated the cell lines with a γ-secretase inhibitor. Expression of the constitutively active Notch-1 reduced proliferation and expression of the DN Notch-1 reduced apoptosis in vitro. However, there was only a small difference in the volume of tumors that formed when the cell lines expressing these constructs were implanted in nude mice. Xenograft tumors derived from the cell lines expressing DN Notch-1 exhibited a neural phenotype. Treatment with a γ-secretase inhibitor caused similar changes as expression of the DN construct. Notch signaling plays a role in cell differentiation, proliferation, and apoptosis in Ewing sarcoma, but its inhibition is only associated with a small change in tumor growth potential.